2019
DOI: 10.1534/genetics.119.302452
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the PCNA DNA Polymerase Clamp ofSaccharomyces cerevisiaeReveal Complexities of the Cell Cycle and Ploidy on Heterochromatin Assembly

Abstract: In Saccharomyces cerevisiae, transcriptional silencing at HML and HMR maintains mating-type identity. The repressive chromatin structure at these loci is replicated every cell cycle and must be re-established quickly to prevent transcription of the genes at these loci. Mutations in a component of the replisome, the proliferating cell nuclear antigen (PCNA), encoded by POL30, cause a loss of transcriptional silencing at HMR. We used an assay that captures transient losses of silencing at HML and HMR to perform … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 56 publications
7
32
0
Order By: Relevance
“…It has also been reported that several PCNA mutations disrupting the PCNA-CAF-1 interaction, together with cac1Δ showed synergistic defects in the silenced state of the HMR region, suggesting that PCNA may contribute to the maintenance of heterochromatin silencing, which is partially independent of the CAF-1-mediated nucleosome assembly pathway [93]. Similar results were observed using the CRASH (Cre-reported altered states of heterochromatin) system, which traced the transient events of silencing loss to the heterochromatin region [111]. It would be interesting to test whether there are other factors that interact with PCNA and that promote RC nucleosome assembly.…”
Section: Pcna: Marking the Replication Fork For Caf-1-mediated Nucleosupporting
confidence: 70%
“…It has also been reported that several PCNA mutations disrupting the PCNA-CAF-1 interaction, together with cac1Δ showed synergistic defects in the silenced state of the HMR region, suggesting that PCNA may contribute to the maintenance of heterochromatin silencing, which is partially independent of the CAF-1-mediated nucleosome assembly pathway [93]. Similar results were observed using the CRASH (Cre-reported altered states of heterochromatin) system, which traced the transient events of silencing loss to the heterochromatin region [111]. It would be interesting to test whether there are other factors that interact with PCNA and that promote RC nucleosome assembly.…”
Section: Pcna: Marking the Replication Fork For Caf-1-mediated Nucleosupporting
confidence: 70%
“…Then, 3xV5-AID2:KanMX was amplified from pVG497 (a gift from Vincent Guacci and Douglas Koshland) with primers that included homology to MCD1 , followed by transformation. The mutant allele HML* was synthesized as a DNA gene block (Integrated DNA Technologies) and integrated using CRISPR-Cas9 technology as previously described ( Brothers and Rine, 2019 ). The EBD sequence was amplified by PCR from cre-EBD78 in the strain UCC5181 ( Lindstrom and Gottschling, 2009 ) with primers that included homology to SIR3, then transformed using CRISPR-Cas9.…”
Section: Methodsmentioning
confidence: 99%
“…Protein extraction and immunoblotting were performed as previously described (Brothers and Rine, 2019). The primary antibodies used were 1:20,000 Rabbit anti-Hexokinase (Rockland #100-4159; Limerick, PA) and 1:2,500 Mouse anti-V5 (Thermo Fisher Scientific R960-25).…”
Section: Protein Extraction and Immunoblottingmentioning
confidence: 99%
“…Whereas PCNA was originally defined as the processivity factor for DNA polymerases, it is now known to regulate virtually every aspect of chromosomal maintenance, including DNA replication, recombination, repair, and chromatin structure (reviewed in references 59 and 60 ). POL30 is an essential gene in S. cerevisiae , but a number of mutant alleles have been generated and shown to exhibit aberrant DNA damage repair and elevated rates of mutation and recombination, among other defects ( 75 78 ). A “Decreased Abundance by mRNA Perturbation” (DAmP) POL30 allele has also been generated, and while its phenotype with respect to genome stability has not been described, large-scale genetic analyses suggest that it behaves similarly to null mutants in nonessential DNA replication genes, such as RAD27 , POL32 , and ELG1 ( 79 ).…”
Section: Discussionmentioning
confidence: 99%